If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 1) = 56 + -1(2x + 1) Reorder the terms: (1 + 2x) = 56 + -1(2x + 1) Remove parenthesis around (1 + 2x) 1 + 2x = 56 + -1(2x + 1) Reorder the terms: 1 + 2x = 56 + -1(1 + 2x) 1 + 2x = 56 + (1 * -1 + 2x * -1) 1 + 2x = 56 + (-1 + -2x) Combine like terms: 56 + -1 = 55 1 + 2x = 55 + -2x Solving 1 + 2x = 55 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 1 + 2x + 2x = 55 + -2x + 2x Combine like terms: 2x + 2x = 4x 1 + 4x = 55 + -2x + 2x Combine like terms: -2x + 2x = 0 1 + 4x = 55 + 0 1 + 4x = 55 Add '-1' to each side of the equation. 1 + -1 + 4x = 55 + -1 Combine like terms: 1 + -1 = 0 0 + 4x = 55 + -1 4x = 55 + -1 Combine like terms: 55 + -1 = 54 4x = 54 Divide each side by '4'. x = 13.5 Simplifying x = 13.5
| 37x^2-3x+88=0 | | 55-x+28=17 | | x+2y+2z=70 | | 16x-3=9+5x | | x+2x=2x+30 | | 5m-(6w+9)=11 | | 7-3x=5x+19 | | 5p-7=4p+3 | | 4m-5=6m+d | | (2x+1)+y=56 | | 16-3p=-21 | | 110+(3x-20)=180 | | 4x+12+34=180 | | 9x-8y=16 | | x^3-5x^2+2x+10=0 | | x^3-5x+2x^2+10=0 | | x^3-15=39 | | 12+x-x^2= | | 20-x-x^2= | | 14-5x-x^2= | | 9(x-4)+2(1+4x)=0 | | 12+4x-x^2= | | 2a-10=-8 | | 5-4x-x^2= | | -5(-3-x)-12=3(1+11x) | | 4x+7=6x-2 | | -11+8x=5x+7 | | 2x-45=15 | | -4x+-3(x-5)=8x | | 8+2x-x^2= | | 8x-9=8(x-1)+1 | | 2x-21x+20=0 |